Slow-to-fast transition of giant creeping rockslides modulated by undrained loading in basal shear zones - Federico Agliardi (Nature Portfolio, 2020)
Giant rockslides creep slowly for centuries and then can fail catastrophically, posing major threats to society. Here, the authors use observational and experimental evidence to quantitatively capture the full spectrum of giant rockslide behaviour until collapse, that is modulated by hydro-mechanical response to short-term fluid pressure perturbations.